2014
DOI: 10.1007/s11096-014-9953-6
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of use of QT-interval prolonging drugs in psychiatry in Belgium

Abstract: Drug combinations that are associated with QT-prolongation are frequently used in the chronic psychiatric setting. Persistent efforts should be undertaken to provide caregivers with clear guidelines on how to use these drugs in a responsible and safe way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…Moreover, haloperidol and domperidone, which both have a definite risk of TdP, were among the most frequently prescribed drugs at discharge, alone and in combination. The co-prescription of an antipsychotic drug with another drug of the same class with a risk of QT prolongation is in line with the findings of Vandael et al [32], in which a high association between antipsychotics and other antipsychotics or antidepressants was found, perhaps because they conducted the study in six psychiatric hospitals in Belgium. In their study, the most frequent combination was with furosemide.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, haloperidol and domperidone, which both have a definite risk of TdP, were among the most frequently prescribed drugs at discharge, alone and in combination. The co-prescription of an antipsychotic drug with another drug of the same class with a risk of QT prolongation is in line with the findings of Vandael et al [32], in which a high association between antipsychotics and other antipsychotics or antidepressants was found, perhaps because they conducted the study in six psychiatric hospitals in Belgium. In their study, the most frequent combination was with furosemide.…”
Section: Discussionsupporting
confidence: 88%
“…To our knowledge this is one of the first large scale investigations to assess the real life (co-)prescriptions of QT-drugs in geriatric patients. While the prevalence of QT-drugs has frequently been assessed in psychiatric patients, because many antidepressants and antipsychotics are known for QT-prolongation, only a few studies investigated the burden of risky QT-drugs selectively in geriatric patients [ 26 , 30 , 31 ]. Lubart et al observed QT-prolongations in 30% of elderly residents in long-term care geriatric wards, which were associated with congestive heart failure and the use of hypnotics [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relationships between individual antipsychotics and QTc prolongation remain controversial (Ramos‐Rios et al ., ; Vandael et al ., ). In this study, thioridazine, clozapine, sulpiride, and chlorpromazine increased the risk of QTc prolongation, partly replicating earlier findings (Yang et al ., ; Vandael et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The relationships between individual antipsychotics and QTc prolongation remain controversial (Ramos‐Rios et al ., ; Vandael et al ., ). In this study, thioridazine, clozapine, sulpiride, and chlorpromazine increased the risk of QTc prolongation, partly replicating earlier findings (Yang et al ., ; Vandael et al ., ). Because of its especially strong QTc prolonging effect by blocking the delayed rectifier potassium channel in the myocardium leading to abnormal repolarization (Reilly et al ., ), thioridazine has been removed from the market in many Western countries.…”
Section: Discussionmentioning
confidence: 99%